The Effect of Echinococcus granulosus on TP53 and CTNNB1genes Sequence Alteration among hepatocellular Carcinoma Patients - Zaynab Kh. Rasheed (Journal of Global Pharma Technology, 2019)
Echinococcus granulosus is one of the small tap worms that causes Hydatid cyst. This study was planned for detection of the incidence among cancer patients at Tumor unit in Baghdad medical city. Eleven samples of liver biopsy out of 40 specimens taken from patients with liver cancer in this study. All patients were suffering from Hydatid cyst infection Patients of migratory encampment in and around Baghdad city Kirkuk, Diyala, and Tikrit Hospitals, suffering from hydatidosis. The present study showed that the predominance of hydatidosis was in the patients whose ages ranged between (≤20-60) years. The sensitivity and specificity of ELISA with hydatid cyst IgG were 96%. While Casoin test (immediate hyper sensitivity skin test) was 100%. The majority incidence was recorded between (50-60) years. The study showed that the predominance of hydatidosis was higher in females 28(70%), than males12 (30%). Analysis of the gene sequence showed that there were genetic mutations occurred in the hepatic cells, and several locations underwent change in genetic sequence including TCC to TCT in exon 147(5), GGT to AGT in exon 152(5), ACT to CCT in exon 160(5), TAT to TGT in exon 203(6),ATG to CTG in exon 235(7).Keywords: TP53 gene, Mutation, Tumor, Hydatid cyst, Gene sequencing.